Synthesis of Chromone-Related Pyrazole Compounds - Santos, Clementina M. M. (Molecules, 2017)
Chromones, six-membered oxygen heterocycles, and pyrazoles, five-membered two-adjacent-nitrogen-containing heterocycles, represent two important classes of biologically active compounds. Certain derivatives of these scaffolds play an important role in medicinal chemistry and have been extensively used as versatile building blocks in organic synthesis. In this context, we will discuss the most relevant advances on the chemistry that involves both chromone and pyrazole rings. The methods reviewed include the synthesis of chromone-pyrazole dyads, synthesis of chromone-pyrazole-fused compounds, and chromones as starting materials in the synthesis of 3(5)-(2-hydroxyaryl)pyrazoles, among others. This review will cover the literature on the chromone and pyrazole dual chemistry and their outcomes in the 21st century.